Uterine Necrosis After Uterine Artery Embolization (UAE) - Rare Entity with a Dilemma - Shama Chaudry; Navaira Azeem; Eugen Khang (ziauddin University, 2024)
Uterine artery embolization (UAE), a minimally invasive procedure used for controlling and managing profuse bleeding in conditions like uterine fibroids, and uterine hemorrhage, in cases of intractable postpartum hemorrhage (PPH). A wide array of complications due to UAE includes pulmonary embolism, uterine ischemia, necrosis, sepsis, and death. A 27 years old married woman (parity 1+2) presented with complaints of a mass protruding of the vagina with dirty brown vaginal discharge. Following UAE was done for postpartum hemorrhage (PPH) she had developed fever and burning micturition on which ultrasound was done to show an anteverted, enlarged, bulky uterus, with multiple endogenic foci, with endometrial canal and adjacent myometrium suggestive of infective pathology. In this case report complications of UAE for the management of PPH were discussed, however, research is required to comprehend the causes of uterine necrosis following uterine artery embolization and its management. Keywords: Uterine Artery Embolization; Postpartum Hemorrhage; Uterine Necrosis; Pathology.